2023
DOI: 10.1021/acs.organomet.3c00007
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Carbonylation of Amines with Mo(CO)6 as the Carbonyl Source

Abstract: Catalytic carbonylation of transition metals is widely used as an effective means to synthesize carbonyl-containing compounds. In this article, we introduce a method for the synthesis of N,N′-diphenyl urea and N-phenyl carbamate by transition-metal-catalyzed carbonylation. Here, we use Mo(CO)6 as a safe and stable carbonyl source to introduce the reaction to produce carbonylation products and achieve the selective formation of N,N′-diphenylurea and N-phenylcarbamate under mild conditions. Mechanistic investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…In addition, under standard conditions, the reaction of N -phenylformamide 8 14 with 2a only afforded a low yield of 3aa . These results indicated that the urea 4 a ,7 is the most likely intermediate in the carbonylative synthesis of carbamates.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…In addition, under standard conditions, the reaction of N -phenylformamide 8 14 with 2a only afforded a low yield of 3aa . These results indicated that the urea 4 a ,7 is the most likely intermediate in the carbonylative synthesis of carbamates.…”
Section: Resultsmentioning
confidence: 81%
“…1 Thus, the development of an efficient methodology for accessing structurally diverse carbamates has attracted considerable attention from both academic and industrial perspectives. Among the numerous protocols developed, 2–8 catalytic carbonylative coupling of amines and alcohols with CO for the synthesis of carbamates has been extensively studied in terms of their atom and step economy. 3–8 In this context, while notable advances have been achieved regarding the oxidative carbonylation of amines with alcohols and CO using different transition metal catalysts (Pd, Rh, Au, etc .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The oxidative carbonylation of amines necessitates the presence of oxidants, such as molecular oxygen, nitro compounds, iodine, quinone, its derivatives, or unsaturated organic substances. , Among these, molecular oxygen serves as the primary oxidant. This reaction entails a mixture of CO and O 2 , which can be potentially explosive within a specific concentration range.…”
Section: Production Process Of Isocyanatementioning
confidence: 99%